Time-resolved single-cell analysis of Brca1 associated mammary tumourigenesis reveals aberrant differentiation of luminal progenitors - Karsten Bach (Nature Portfolio, 2021)
BRCA1 driven breast cancer arises from luminal progenitor cells but how BRCA1 loss-of-function affects the luminal progenitor cell state during premalignant stages of the disease is still unclear. Here, the authors demonstrate an aberrant differentiation of luminal progenitors towards a partial secretory luminal cell phenotype that occurs in a Brca1 deficient mouse model of breast cancer at early stages of tumour initiation and in breast cells from BRCA1 carriers.